Development of an anti-Acinetobacter baumannii biofilm phage cocktail: Genomic adaptation to the Host - Blasco, L. (2022)
The need for alternatives to antibiotic therapy due to the emergence of multidrug resistant bacteria (MDR), such as the nosocomial pathogen Acinetobacter baumannii, has led to the recovery of phage therapy. In addition, phages can be combined in cocktails to increase the host range. In this study, the evolutionary mechanism of adaptation was utilized in order to develop a phage adapted to A. baumannii, named phage Ab105-2phiCI404ad, from a mutant lytic phage, Ab105-2phiCI, previously developed by our group. The whole genome sequence of phage Ab105-2phiCI404ad was determined, showing that four genomic rearrangements events occurred in the tail morphogenesis module affecting the ORFs encoding the host receptor binding sites. As a consequence of the genomic rearrangements, 10 ORFs were lost and four new ORFs were obtained, all encoding tail proteins; two inverted regions were also derived from these events. The adaptation process increased the host range of the adapted phage by almost three folds. In addition, a depolymerase-expressing phenotype, indicated by formation of a halo, which was not observed in the ancestral phage, was obtained in 81% of the infected strains. A phage cocktail was formed by combining this phage with the A. baumannii phage vB_AbaP_B3, known to express a depolymerase. Both the individual phages and the phage cocktail showed strong antimicrobial activity against 5 clinical strains and 1 reference strain of A. baumannii tested. However, in all cases resistance to the bacterial strains was also observed. The antibiofilm activity of the individual phages and the cocktail was assayed. The phage cocktail displayed strong antibiofilm activity.